Ionospheric TEC Weather Map Over South America - Takahashi, H.; Wrasse, C. M.; Denardini, C. M.; Padua, M. B.; Paula, E. R. de; Costa, S. M. A.; Otsuka, Y.; Shiokawa, K.; Galera Monico, J. F. [UNESP]; Ivo, A.; Sant'Anna, N. (Amer Geophysical Union, 2016)
Ionospheric weather maps using the total electron content (TEC) monitored by ground-based Global Navigation Satellite Systems (GNSS) receivers over South American continent, TECMAP, have been operationally produced by Instituto Nacional de Pesquisas Espaciais's Space Weather Study and Monitoring Program (Estudo e Monitoramento Brasileiro de Clima Especial) since 2013. In order to cover the whole continent, four GNSS receiver networks, (Rede Brasileiro de Monitoramento Continuo) RBMC/Brazilian Institute for Geography and Statistics, Low-latitude Ionospheric Sensor Network, International GNSS Service, and Red Argentina de Monitoreo Satelital Continuo, in total similar to 140 sites, have been used. TECMAPs with a time resolution of 10min are produced in 12h time delay. Spatial resolution of the map is rather low, varying between 50 and 500km depending on the density of the observation points. Large day-to-day variabilities of the equatorial ionization anomaly have been observed. Spatial gradient of TEC from the anomaly trough (total electron content unit, 1TECU=10(16)elm(-2) (TECU) <10) to the crest region (TECU>80) causes a large ionospheric range delay in the GNSS positioning system. Ionospheric plasma bubbles, their seeding and development, could be monitored. This plasma density (spatial and temporal) variability causes not only the GNSS-based positioning error but also radio wave scintillations. Monitoring of these phenomena by TEC mapping becomes an important issue for space weather concern for high-technology positioning system and telecommunication.
Keywords: ionospheric weather; TEC mapping; plasma bubbles; GNSS positioning